Les Teneurs Métalliques Et Paramètres Physico- Chimiques De L’eau Et Du Sédiment De Oued Beht, Au Niveau De Sidi Kacem Et De Oued R’dom Au Niveau De Sidi Slimane - Aziz, Qaouiyid; Hajar, Hmima; Kaoutar, Houri; Ilham, Saad; El Hassania, Saad; Fadli, Mohamed (European Scientific Journal, ESJ, 2016)
In the present study we evaluated the physicochemical characteristics and the degree of the metallic contamination, in spring and summer, of the areas exposed to discharges of urban and industrial waste water: Sidi Slimane which rejects its waste in Oued Beht, and Sidi Kacem, which rejects its waste on Oued R’dom. The two water courses are tributaries of Oued Sebou, the most polluted river in Morocco. For physico-chemistry, the results showed that for both areas exposed to waste, the pH is alkaline, the temperature is between 20 ° C to 26 ° C depending on the season, the average conductivity is very high, dissolved oxygen levels are low especially in summer, BOD5 and BCO show that the fraction of non-biodegradable waste is no negligible, the water hardness is not very high but it is more calcium than magnesium, an average level of alkalinity, an average level of orthophosphate, sulfates and nitrogenous substances. Similarly, the results showed that in areas exposed to discharges of the two cities, the metal contamination of the sediment is higher than that of water contamination although this remains nearly an average degree of contamination in these two compartments of the biotope. Furthermore, in the study areas, Oued R’dom showed a slightly higher assimilative capacity than Oued Beht except for Aluminium and Chrome. Also note that, for the same area of study, the factor "Season" influences the physico-chemical and the values of metallic chemical elements of the water and sediment.